2014
DOI: 10.7554/elife.01812
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the SAS-6 cartwheel hub from Leishmania major

Abstract: Centrioles are cylindrical cell organelles with a ninefold symmetric peripheral microtubule array that is essential to template cilia and flagella. They are built around a central cartwheel assembly that is organized through homo-oligomerization of the centriolar protein SAS-6, but whether SAS-6 self-assembly can dictate cartwheel and thereby centriole symmetry is unclear. Here we show that Leishmania major SAS-6 crystallizes as a 9-fold symmetric cartwheel and provide the X-ray structure of this assembly at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 58 publications
3
74
0
Order By: Relevance
“…e), f). Procentriole assembly, PDBid: 4CKP, [33,34]. According to these authors, this ring interacts with others both by stacking and by lateral association.…”
Section: Discussionmentioning
confidence: 99%
“…e), f). Procentriole assembly, PDBid: 4CKP, [33,34]. According to these authors, this ring interacts with others both by stacking and by lateral association.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray crystallography studies showed that SAS-6 comprises a globular N-terminal domain followed by a long coiled coil ( Figure 1) and a C-terminal disordered region. SAS-6 strongly dimerises in vitro and in vivo via its coiled-coil domain, and protein dimers further interact via their N-terminal domains to form oligomers with 9-fold radial symmetry on average [28][29][30][31]. The SAS-6 N-terminal domain bears strong structural resemblance to similar domains of XRCC4 and XLF (Figure 2), proteins involved in DNA repair and non-homologous end joining.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there exist three crystallographic models of the CrSAS-6 NN interface and one of the CrSAS-6 CC interface [31]; thus, three different oligomer variants can be built depending on the NN interface model employed resulting in 9.6-to 10.1-fold radial symmetry. Similarly, when DrSAS-6 oligomers are built from available crystal structures a variation in oligomer architecture is observed, with DrSAS-6 forming either an 8-fold symmetric shallow spiral or an 8-fold symmetric ring [29], Most SAS-6 oligomers resolved to date are highly reminiscent of cartwheel rings, with a central hub derived from the N-terminal globular domains and the SAS-6 coiled coils comprising the cartwheel spokes [28,29,31]. Furthermore, disruption of SAS-6 oligomerisation abrogates formation of the central centriole scaffold and strongly hinders organelle assembly [29,31].…”
Section: Sas-6 Ringsmentioning
confidence: 99%
See 2 more Smart Citations